The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3892/ol.2020.11635
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA SNHG7 inhibits NLRP3‑dependent pyroptosis by targeting the miR‑34a/SIRT1 axis in liver cancer

Abstract: Long non-coding RNA small nucleolar RNA host gene 7 (SNHG7) is involved in a variety of different types of cancer; however, the role of SNHG7 during liver cancer progression is not completely understood. The aim of the present study was to investigate the functional role and regulatory mechanism underlying SNHG7 during liver cancer. A total of 25 paired hepatocellular carcinoma (HCC) tumor tissues and adjacent normal tissues were collected. Reverse transcription-quantitative PCR and western blotting were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 34 publications
1
57
0
Order By: Relevance
“…Several studies have reported that the activation of the NLRP3/Caspase-1 pathway is associated with tumor progression (24)(25)(26)(27). Wang et al (25) found that when the NLRP3 inflammasome is activated, Caspase-1 is spliced to further activate the Akt, GSK-3p, ERK1/2 and CREB signaling pathways to promote tumor proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that the activation of the NLRP3/Caspase-1 pathway is associated with tumor progression (24)(25)(26)(27). Wang et al (25) found that when the NLRP3 inflammasome is activated, Caspase-1 is spliced to further activate the Akt, GSK-3p, ERK1/2 and CREB signaling pathways to promote tumor proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological levels of NLRP3 activation protects the body's inflammatory immune system via activation of Caspase-1, whereas uncontrolled activation will lead to dysregulated inflammation, autoimmune diseases, neurodegenerative diseases, and even malignant tumors (20)(21)(22)(23)(24). Recently, a number of studies have reported that the overactivation of NLRP3 is closely associated with the progression of several malignant tumors (24)(25)(26)(27). To date, there are numerous studies on the downstream effects of NLRP3 (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…In liver cancers, SNHG7 worked as a ceRNA of miR-34a, and SIRT1 was proved to be a direct target of miR-34a. Interference with SNHG7 down-regulated the expression of SIRT1, but up-regulated the levels of NLRP3, caspase-1, and interleukin-1beta, which induced pyroptosis, suggesting NLRP3-dependent pyroptosis was induced through SNHG7/miR-34a/SIRT1 signaling pathway during liver cancer [ 64 ]. Kcnq1ot1 regulated the level of caspase-1 by working as a sponge of miR-214-3p.…”
Section: Pyroptosis In Cancer Metastasismentioning
confidence: 99%
“… 90 , 91 Pyroptosis is connected to the clearing of various bacterial and viral infections by eliminating intracellular replication niches and increasing the host’s defensive responses. 92 The correct pyrolysis pathway may increase pathogen clearance efficiency and promote adaptive immune stimulation. Researchers believe that inducing tumor pyroptosis may be a potential treatment strategy.…”
Section: The Role Of Lncrnas In Pyroptosismentioning
confidence: 99%